The role of therapeutic endoscopy in the management of oesophageal varices in children and adults: does it mean no more open surgery - De zoysa, M.I.M.; Samarasekera, D.N.; Sheriffdeen, A.H. (My University, 2012)
Oesophageal varices is the commonest cause of acute upper gastrointestinal bleeding in Sri Lanka. Endoscopic sclerotherapy(EST) and rubber band ligation (RBL) have become the main treatment modalities, as they carry a lower morbidity and mortality compared to shunt surgery.